Financial Factors Affecting Major Subject Choice - Waqas Ahmed; Muhammad Ejaz; Maria Siddique; Shahwana Sadaf (International Journal of Business and Economic Affairs, 2022)
Choice of major subject describes an important process of individual behavior in the presence of many alternatives. Purpose of this work was to identify and understand the financial factors and sources that students apply when they decide on the choice of major at the time of admission to BS degrees in Post Graduate colleges of KPK. Various factors such as (i) Family Income, (ii) Type of Family Income, (iii) Affordability, (iv) Loan Taken, (v) Scholarship, (vi) Management of Educational Expenses (vii) Special Arrangements for Educational Expenses (viii) Cost Specifically Fee, (ix) Out of Pocket Expenses; and (x) Traveling Expenses are the variables used for addressing the relationship between factors and major choice. Through a structured questionnaire, 1978 respondents shared their views about the financial factors influencing their major subject choice decision. Through applying the Descriptive Analysis and Logit Model, odd ratios of family income, affordability, and traveling expenses positively affect the student’s choice of major subject in the field of Natural and Physical Sciences. While the type of family income, scholarship, management of educational expenses, cost (fee), and out-of-pocket expenses significantly but negatively impact the student’s decision. It indicates that students will likely choose the subjects from Humanities and Social Sciences. It is suggested that students should be given financial freedom and power to assess the existing opportunities better and explore the new horizon to become better skilled human capital.